Shifting Paradigms: A Deep Dive Into Public Perceptions of Gender-affirming Surgery - Justin M. Camacho, MBA; Michael Alfertshofer, MD; Heli S. Patel, MBA; Daniel Najafali, BS; Noelle Thompson, BS; Victoria Stoffel, MS; Chris M. Reid, MD; Michael Alperovich, MD; Samuel Knoedler, BS; Leonard Knoedler, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Given the growing demand for gender-affirming surgery (GAS) in recent years, it is essential to explore the public perceptions of GAS. Understanding the public’s opinions and attitudes toward GAS will provide valuable insights for shaping educational initiatives to enhance public knowledge and awareness. Methods:. This cross-sectional study used the Prolific Academic platform to distribute an online survey among adult participants residing in the United States in August 2023. Results:. Of 1005 completed survey responses, 50% of respondents were 41 years of age or older, 51% were women, and 73% were White. A total of 18% identified as part of the LGBTQIA+ community, and most (37%) resided in the southern United States. The majority of participants (78%) did not personally know anyone who underwent GAS, and 74% believed that plastic surgeons mainly perform GAS. Only 22% felt healthcare professionals were well qualified to provide gender-affirming care. Media’s effect on GAS acceptance was assessed to be mostly negative (33%) or very negative (12%). About 33% favored both public and private health insurance coverage for GAS, whereas 35% opposed insurance coverage. Most respondents strongly agreed (32% and 34%) or agreed (33% and 37%) that GAS aligns with gender identity and improves mental health. Regarding minimum age, most partakers (43%) supported 18 years, whereas 38% endorsed 21 years. Conclusions:. This study sheds light on the public perceptions of GAS. These insights underscore the need for targeted educational efforts to increase awareness, rectify misconceptions, and promote a deeper understanding of GAS within society.